Materials and finishes selection for dancing studio in relation to acoustic and aesthetic aspects / Sonia Raj Mohamad Jufri Erethinavelan - Mohamad Jufri Erethinavelan, Sonia Raj (2021)
Dance is an art form or activity that uses the body and the diversity of movement in which the body is capable. Dancer listens to sounds from pianos, stereos, human voice, and floor contact like in tap dance. These all make an essential contribution to the dancer's overall noise exposure. The issues of this research are that noise exposure cause disturbance to the user. Excessive exposure to noise has implications for our health and well-being, which go well beyond hearing damage. This research aims to identify the appropriate material and finishes specification used concerning acoustic and aesthetic aspects for the dancing studio. There are several objectives of the study that need to be achieved in this research: identifying user satisfaction towards the material and finishes used and investigating the types of material and finishes used to acoustic and aesthetic aspects. The methodology that will be applied is a mixed-method by using a questionnaire survey and an on-site observation to gather information and conclude the findings. This research will benefit the owner, dance community, acoustic consultants and designer to create a better environment studio. For future recommendations, it is suggested to have a quiet environment of dance venue for the user to feel comfortable dancing without noise disruption, as well as considering acoustic design, which plays a vital role in designing dance studios in which the acoustic consultants are responsible for the design process.